2017
DOI: 10.1007/s41465-017-0022-7
|View full text |Cite|
|
Sign up to set email alerts
|

Meditation and Cognitive Ageing: the Role of Mindfulness Meditation in Building Cognitive Reserve

Abstract: Mindfulness-related meditation practices engage various cognitive skills including the ability to focus and sustain attention, which in itself requires several interacting attentional subfunctions. There is increasing behavioural and neuroscientific evidence that mindfulness meditation improves these functions and associated neural processes. More so than other cognitive training programmes, the effects of meditation appear to generalise to other cognitive tasks, thus demonstrating far transfer effects. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 106 publications
(109 reference statements)
2
33
0
Order By: Relevance
“…The interviews revealed that participants were cognitively stimulated and emotionally boosted, potentially increasing resilience. These results are consistent with prior research showing that adults with MCI still have brain plasticity, [20] but the skills learned with mindfulness meditation may specifically build cognitive reserve [61] and enable participants to build resilience for the grim future they may face. In addition, an aspect of enhanced well-being that emerged from the interviews was an improved motivation for being engaged in a new activity and learning a new skill.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The interviews revealed that participants were cognitively stimulated and emotionally boosted, potentially increasing resilience. These results are consistent with prior research showing that adults with MCI still have brain plasticity, [20] but the skills learned with mindfulness meditation may specifically build cognitive reserve [61] and enable participants to build resilience for the grim future they may face. In addition, an aspect of enhanced well-being that emerged from the interviews was an improved motivation for being engaged in a new activity and learning a new skill.…”
Section: Discussionsupporting
confidence: 91%
“…[85] In addition, since our original publications reporting our results of MBSR in adults with MCI [21,22], there has been significant interest in understanding the role mind-body programs play in adults with mild cognitive impairment, dementia, subjective cognitive decline, and in aging in general. [61,[86][87][88][89][90][91][92][93][94][95] A manual of a mindfulness program for adults with dementia has even been published. [96]…”
Section: Discussionmentioning
confidence: 99%
“…The first two looked at identifying and exploring different types of meditation within Theravada, with the second specifically tackling the problem of identifying different techniques with manuscript collections. The third conference was inspired by the documentation of the benefits of mindfulness meditation on the preservation of cognitive reserve in ageing (Malinowski and Shalamanova 2017) and the traditional periods of meditation practice held in certain Theravada communities specifically for their senior generation (Eberhardt 2017; contributions by Khur-Yearn and Wharton to this volume). Versions of a number of the papers that follow were originally aired at one or another of these three events.…”
Section: Origins Of This Volume and Some Of Its Themesmentioning
confidence: 99%
“…Many cognitive enhancements, however, in fact the majority, are freely available. Malinowski and Shalamanova (2017) argue that research into meditation has shown that many cognitive capacities can be enhanced by meditation practices and even halt the effect of aging on the brain. These forms of cognitive enhancement seem to be entirely unproblematic.…”
Section: Human Enhancement Leads To Inequality?mentioning
confidence: 99%